THU0381 Certolizumab pegol is effective in uveitis associated to spondyloarthritis refractory to other tumour necrosis factor inhibitors. (15th June 2017) - Hernández, MV; Mesquida, M; Llorens, V; Maza, M Sainz de la; Blanco, R; Calvo, V; Maiz, O; Blanco, A; Urruticoechea, A; Jiménez, JRDD de Aberásturi; Ahijado, P; Judez, E; et al.
Abstract : Background: Uveitis is one of the most common extra-articular manifestations of patients with spondyloarthritis (SpA). In severe cases, uveitis may require the use of biological therapy, primarily tumor necrosis factors inhibitors (TNFi), being the most currently used infliximab and adalimumab. However, another TNFi such as certolizumab pegol (CZP), with indication for SpA patients, could be an effective option in cases of inefficacy or adverse events to other TNFi, as we have previously reported (1). Objectives: Our objective is to analyze the effectiveness and the safety profile of CZP in patients with refractory SpA-associated-uveitis Methods: Observational, multicentric, retrospective study. We selected all patients with a diagnosis of SpA (including ankylosing spondylitis (AS), psoriatic arthritis (PsA), non-radiographic axial SpA (nr-axSpA) and SpA associated to inflammatory bowel disease (IBD-SpA)) who had refractory uveitis (confirmed by an Ophthalmologist) as main extra-articular manifestation, and who received CZP for at least 6 months. Variables analyzed: age, sex, diagnosis, type of uveitis, duration since the first uveitis episode and number of eyes affected; previous treatment (NSAID, disease-modifying anti-rheumatic drugs (DMARDs), immunossuppressive or biological therapy); outcome, and time to follow-up. Results: Twenty-four eyes of 13 patients (10 men); age 49.5±11.7 (range 29–71 years) were included in the study. Diagnosis were: seven AS, four PsA, one nr-axSpA, and one IBD-SpA. Type of uveitis: 9 anterior, 3 panuveitis, and 1 intermediate uveitis. Mean disease duration was 151±117.1 months (range 5–420). 84.6% patients had previously received biological therapy (46.1% ≥2 biological agents). 61.5% received CZP in monotherapy and 5 patients received concomitant treatment: 4 methotrexate and 1 azathioprine. In all cases CZP was started due to inefficay to previous treatment except for 2 cases whose primary reason was the occurrence of adverse events (one injection site reaction and one development of relapsing polychondritis). After a follow-up of 13.1±6.6 months (range 6–27), 9 patients are still on CZP treatment. Ten eyes showed improvement of visual acuity (41.7%), 10 remained stable and 2 worsened. During the follow-up no serious adverse events were reported. Four cases withdrew CZP treatment: 2 due to worsening of articular symptoms but with no uveitis activity; 1 due to macular edema and 1 due to uveitis activity. One patient switch to infliximab, one to golimumab, and 2 required switch to tocilizumab. In all 13 patients except 2, CZP achieved a good control of SpA activity. Conclusions: CZP demonstrated effectiveness in patients with uveitis-associated to SpA refractory to previous TNFi treatment. References: Llorenç V et al. Ocul Immunol Inflamm. 2016; 24: 167–72. Disclosure of Interest: None declared